KATA PENYUKAT DALAM BAHASA KAMARU - Yohanis Sanjoko (Balai Bahasa Provinsi Papua, 2019)
The classifier word is a word that located behind numeralized and together with the word formed a phrase that called numbers phrase, which possible located in front of the nominal word. The purpose of this study is to describe the form and classification of lassifier words in language of Kamaru. This study uses descriptive method with three stages, namely providing data, data analysis, and presentation of the results of the data analysis. Data analysis conducted after the data netted classified. Applied analysis used apportion method. The result of this study is a form and classification of classifier words in the language of Kamaru, namely (1) the classifier word for animals, (2) the classifier words for objects, and (3) the classifier word for humans. Each further divided into common classifier words and special classifier.